Proceso atención de enfermería en embarazada de 31.5 semanas de gestación más septicemia. - Montiel Uriarte, Jonathan Eduardo (2021)
The current clinical case study of a nursing care process in a pregnant patient of 31.5 weeks of gestation plus 21-year-old septicemia or an apparent antecedent of bacterial vaginosis in the first months of pregnancy in a subacute condition of approximately 8 days of evolution, where it presents a clinical picture where it is complicated hemodynamically so low-flow oxygen therapy is administered, plus nebulizations with ipratropium bromide and sodium chloride, in addition to the administration of metoclopramide, ampicillin, paracetamol betamethasone, clotrimazole in ovum and sulbactam. Through the nursing care process, it was possible to correctly monitor the vital signs and hemodynamic activity of the patient, and the administration of their medications prescribed by the doctor was carried out correctly. The nursing process helps the patient in her rehabilitation and evolves in a favorable way, within the conclusions it was possible to determine the risk factor of septicemia in this type of patients, in addition, it was possible to develop a strategy plan for treatment and used the nursing care process according to the diagnosed pathology, the needs raised by Virginia Henderson were used, in addition to the theory of Nanda, NIC and NOC, which were fundamental in this care process since, although it also helped to determine which were the most important symptoms to correct and treat to avoid further complications in the pregnant patient.